JD‐Next: A valid and reliable tool to predict diverse students' success in law school. Issue 1 (3rd January 2023) - Findley, Jessica; Cimetta, Adriana; Burross, Heidi Legg; Cheng, Katherine C.; Charles, Matt; Balser, Cayley; Li, Ran; Robertson, Christopher
A bstract: Admissions tests have increasingly come under attack by those seeking to broaden access and reduce disparities in higher education. Meanwhile, in other sectors there is a movement towards "work‐sample" or "proximal" testing. Especially for underrepresented students, the goal is to measure not just the accumulated knowledge and skills that they would bring to a new academic program, but also their ability to grow and learn through the program. The JD‐Next is a fully online, noncredit, 7‐ to 10‐week course to train potential JD students in case reading and analysis skills, prior to their first year of law school. This study tests the validity and reliability of the JD‐Next exam as a potential admissions tool for juris doctor programs of education. (In a companion article, we report on the efficacy of the course for preparing students for law school.) In 2019, we recruited a national sample of potential JD students, enriched for racial/ethnic diversity, along with a sample of volunteers at one university ( N  = 62). In 2020, we partnered with 17 law schools around the country to recruit a cohort of their incoming law students ( N  = 238). At the end of the course, students were incentivized to take and perform well on an exam that we graded with a standardized methodology. We collected first‐semester grades as an outcome variable, and compared JD‐Next exam properties to legacy exams now used by law schools (the Law School Admissions Test (LSAT), including converted GRE scores). We found that the JD‐Next exam was a valid and reliable predictor of law school performance, comparable to legacy exams. For schools ranked outside the Top 50, we found that the legacy exams lacked significant incremental validity in our sample, but the JD‐Next exam provided a significant advantage. We also replicated known, substantial racial and ethnic disparities on the legacy exam scores, but estimate smaller, nonsignificant score disparities on the JD‐Next exam. Together this research suggests that, as an admissions tool, the JD‐Next exam may reduce the risk that capable students will be excluded from legal education and the legal profession.